Green synthesis of reduced graphene oxide/Fe3O4/Ag ternary nanohybrid and its application as magnetically recoverable catalyst in the reduction of 4‐nitrophenol. (30th March 2017) - Thu, Tran Viet; Ko, Pil Ju; Nguyen, To Van; Vinh, Nguyen Thanh; Khai, Doan Minh; Lu, Le Trong
Abstract : Materials having both magnetic and catalytic properties have shown great potential for practical applications. Here, a reduced graphene oxide/iron oxide/silver nanohybrid (rGO/Fe3 O4 /Ag NH) ternary material was prepared by green synthesis of Ag on pre‐synthesized rGO/Fe3 O4 . The as‐prepared rGO/Fe3 O4 /Ag NH was characterized using Fourier transform infrared spectroscopy, X‐ray diffractometry, Raman spectroscopy, vibrating sample magnetometry, transmission electron microscopy and energy‐dispersive X‐ray spectroscopy. rGO sheets were covered with Fe3 O4 (8–16 nm) and Ag (18–40 nm) nanoparticles at high densities. The mass percentages were 13.47% (rGO), 62.52% (Fe3 O4 ) and 24.01% (Ag). rGO/Fe3 O4 /Ag NH exhibited superparamagnetic behavior with high saturated magnetization (29 emu g −1 at 12 kOe), and efficiently catalyzed the reduction of 4‐nitrophenol (4‐NP) with a rate constant of 0.37 min −1, comparable to those of Ag‐based nanocatalysts. The half‐life of 4‐NP in the presence of rGO/Fe3 O4 /Ag NH was ca 1.86 min. rGO/Fe3 O4 /Ag NH could be magnetically collected and reused, and retained a high conversion efficiency of 94.4% after the fourth cycle. rGO/Fe3 O4 /Ag NH could potentially be used as a magnetically recoverable catalyst in the reduction of 4‐NP and environmental remediation. Abstract : A superparamagnetic reduced graphene oxide/iron oxide/silver nanohybrid was synthesized using a green method. The nanohybrid efficiently catalyzed the reduction of 4‐nitrophenol and could be magnetically recovered and reused multiple times.